Al-Kalimat fî Al-‘Arabiyyat ‘inda Al-Nuhât Al-Mutaqaddimîn wa Al-Mutaakhkhirîn wa Al-Mu’aṣṣirîn (Dirâsat Al-Muqâranat) - Aang Saeful Milah (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
When the Arabs set grammar, the Syriac linguists preceded them several centuries in establishing rules towards them. Perhaps one issue is the one taken by the Arab linguists on Syriac, but the issue of dividing the word into three sections only: name, action, and character. The advanced Arab grammarians handed over this issue from the first day, and do not argue with it. Those who denied this issue and corrected the mistake are the modern European linguists who began to set rules for their languages ​​after the Arabs for hundreds of years. For example, in French, divide the word into nine sections. The researcher tries to present this research from three centuries and is the advanced and the late and contemporaries. The researcher begins with the concept of the word and then divides it into the Arabic linguists.